Isolation And Characterization Of Heterotrophic Bacteria From Indah Kalangan Beach, Central Tapanuli - fadilah, Wanda; ., Rasyida; Mayasari, Ulfayani (Metamorfosa: Journal of Biological Sciences, 2022)
This research aims to determine the presence of heterotrophic bacteria in the coastal waters of Indah Kalangan, Central Tapanuli and what genus of heterotrophic bacteria were found in the coastal waters of Indah Kalangan, Central Tapanuli. The working procedure in this research is the characterization of bacterial morphology, gram staining and also characterization based on biochemical tests. The descriptive method will be used in the data analysis process using Bergey's Manual of Determinative Bacteriology 8 th Edition, Bergey's Manual Of Systematic Bacteriology 2 nd Edition and journals. The results of this study obtained 16 isolates of heterotrophic bacteria, of which 13 bacterial isolates belonged to the Bacillus genus and 3 bacterial isolates belonged to the Vibrio genus. The results showed that the coastal waters of Indah Kalangan contained heterotrophic bacteria with the genus Bacillus and the genus Vibrio .   Keywords : Heterotrophic Bacteria, Bacillus , Vibrio , Indah Kalangan Beach